Police-Community Relationship in Kuwait: Public Relations Perspective - Almutairi, Talal (2013)
This thesis explores the current police-community relationships in Kuwait where no previous research on this particular topic is known. Therefore, the overall goal of this thesis is to both describe the current relationship between the Kuwaiti police and the community and, based on the results, provide suitable recommendations to help forge and maintain positive relations. In order to accurately illustrate the current relationship, this thesis utilises three major theoretical concepts: the co-creational approach (relational approach and community theory), systems theory, and social exchange theory. Habermas’s Theory of Communicative Action (TCA) was also discussed to shed light on the power dynamic of the police-community relationship. Although these theories differ in their approach, they present the public relations approach through a shared focal point – relationships, which is the primary focus of this research. In a qualitative approach, twenty-two participants were interviewed and their answers coded and transcribed. Particular attention was paid to the sampling of interview participants through the use of the qualitative sampling techniques of quota and purposive sampling. In the analysis of data, three themes, Faith, Communitarianism, and Optimism represent an important and special context for the public relations theorist. They contribute to our understanding of public relations in the context of Kuwaiti police-community relations. Furthermore, the relational elements of trust, satisfaction, control mutuality and commitment are integrated with the three aforementioned themes. This analytical framework strengthened the analysis by adding a comparative and universal perspective. The main findings of this research are the key attributes affecting the police- community relationship in Kuwait, such as trust, satisfaction, commitment, control, mutuality, and the worldviews through which the participants regard the police: Faith, Communitarianism, and Optimism. Furthermore, the implication of this thesis goes beyond that of the police-community relationship in that country. It also provides a thorough discussion regarding 1) public relations theory and practice, and 2) a thematic analysis of the Kuwaiti police. This thesis adds to public relations theories as it extends the body of knowledge of public relations to a specific context of police public relations in Kuwait. This will help to round-out existing police PR data, especially by adding a Middle Eastern and Arabic perspective to otherwise Western theories (e.g. relational, community, systems and social exchange). Furthermore, this thesis demonstrates how environmental factors (Kuwaiti history, culture and economics) influence organisation-public relations. This thesis explores an essential area for Kuwaiti police that has not been explored before. Through the investigation of interview data, this thesis provides a snapshot of the current police-community relationship, highlighting important issues that are obstacles to a better police-community relationship. The most salient two are (1) police force behaviour, and (2) the organization's communication style. It is recommended that Kuwaiti police should adapt the community policing approach. This thesis proposes that adapting the community policing approach will help to improve behaviour and communication styles by addressing root issues. This adjustment will require the police organisation to adjust its goals and mission so as to become aligned with that of the community's goals and mission